Tumor-activated carrier-free prodrug nanoparticles for targeted cancer Immunotherapy: Preclinical evidence for safe and effective drug delivery - Shim, Man Kyu; Yang, Suah; Sun, In-Cheol; Kim, Kwangmeyung (Elsevier BV, 2022)
As immunogenic cell death (ICD) inducers initiating antitumor immune responses, certain chemotherapeutic drugs have shown considerable potential to reverse the immunosuppressive tumor microenvironment (ITM) into immune-responsive tumors. The application of these drugs in nanomedicine provides a more enhanced therapeutic index by improving unfavorable pharmacokinetic (PK) profiles and inefficient tumor targeting. However, the clinical translation of conventional nanoparticles is restricted by fundamental problems, such as risks of immunogenicity and potential toxicity by carrier materials, premature drug leakage in off-target sites during circulation, low drug loading contents, and complex structure and synthetic processes that hinder quality control (QC) and scale-up industrial production. To address these limitations, tumor-activated carrier-free prodrug nanoparticles (PDNPs), constructed only by the self assembly of prodrugs without any additional carrier materials, have been widely investigated with distinct advantages for safe and more effective drug delivery. In addition, combination immunotherapy based on PDNPs with other diverse modalities has efficiently reversed the ITM to immune-responsive tumors, potentiating the response to immune checkpoint blockade (ICB) therapy. In this review, the trends and advances in PDNPs are outlined, and each self-assembly mechanism is discussed. In addition, various combination immunotherapies based on PDNPs are reviewed. Finally, a physical tumor microenvironment remodeling strategy to maximize the potential of PDNPs, and key considerations for clinical translation are highlighted.(c) 2022 Elsevier B.V. All rights reserved.